2018
DOI: 10.1055/s-0038-1637762
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus in Otherwise Healthy Prematurely Born Infants: A Forgotten Majority

Abstract: Healthy, premature infants ≤35 weeks' gestational age (wGA) are universally recognized to be at an increased risk of perinatal morbidity and mortality. Serious respiratory syncytial virus (RSV) lower respiratory tract infection imposes an additional burden of illness on these infants following hospitalization. Incurred morbidities relative to term infants include longer lengths of hospital stay, admission to intensive care, and need for oxygen and mechanical ventilation, all of which are associated with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
6
0
3
Order By: Relevance
“…Children born prematurely were found to be at increased risk of RSVH, including those born moderate-late preterm (33-35 wGA), where the incidence was more than double that in term children (4.6% vs. 1.9%, respectively; p < 0.0001). These data support the case for preventive strategies against severe RSV infection in preterm infants [22][23][24]. In addition to established high-risk comorbidities, such as CLD/BPD and CHD, our study provides valuable new data on the increased risk of RSVH in children with Down syndrome (RSVH incidence: 14.8%), cystic fibrosis (12.6%), cerebral palsy (15.5%), and neuromuscular disorders (17.0%), where published data are more scarce [25].…”
Section: Maximal Burden Of Rsvhsupporting
confidence: 76%
“…Children born prematurely were found to be at increased risk of RSVH, including those born moderate-late preterm (33-35 wGA), where the incidence was more than double that in term children (4.6% vs. 1.9%, respectively; p < 0.0001). These data support the case for preventive strategies against severe RSV infection in preterm infants [22][23][24]. In addition to established high-risk comorbidities, such as CLD/BPD and CHD, our study provides valuable new data on the increased risk of RSVH in children with Down syndrome (RSVH incidence: 14.8%), cystic fibrosis (12.6%), cerebral palsy (15.5%), and neuromuscular disorders (17.0%), where published data are more scarce [25].…”
Section: Maximal Burden Of Rsvhsupporting
confidence: 76%
“…Complications necessitating admission to intensive care units in children with RSV are typically respiratory failure due to severe bronchiolitis in young infants (aged <3 months) and children with comorbidities, such as prematurity, chronic lung diseases, congenital heart disease, and neuromuscular diseases. 11 , 12 , 13 , 14 Older infants and children without comorbidities are less likely to be admitted to an intensive care unit than infants aged younger than 3 months and those with comorbidities, and their complications are less well described. 15 Complications comprising severe bacterial infections, pneumothorax, neurological complications, and cardiac manifestations have primarily been reported in case series.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 In a recent review, healthy premature infants 35 wGA were reported to be at higher risk for RSV infections compared with term infants. 22 After the restriction of the AAP guideline and Italian reimbursement system, a study from Italy reported higher number of RSV infections in preterm infants <36 wGA, especially in the presence of specific risk factors. 23 Similarly, an increase in RSV associated hospitalizations in 29 to 34 wGA preterm infants in the United States was reported after the change in AAP guideline.…”
Section: Resultsmentioning
confidence: 99%
“…28 For preterm infants !29 wGA, the chronological age of <3 months during RSV season was also reported as an important risk factor for severe RSV infections in several studies. [22][23][24] In recently published SENTINEL1 study including 1378 infants, the authors reported 82% of RSV hospitalizations within 60 days of birth hospital discharge among infants born during RSV season. 29 Similarly, the chronological age of being 3 months during RSV season was found to be an independent risk factor for RSV infections in our study.…”
Section: Resultsmentioning
confidence: 99%